Democracy and constitutional reform: Deliberative versus populist constitutionalism. (December 2019) - Chambers, Simone
Constitutional reform has been an important means to push populist authoritarian agendas in Hungary, Poland, Turkey and Venezuela. The embrace of constitutional means and rhetoric in pursuit of these agendas has led to the growing recognition of 'populist constitutionalism' as a contemporary political phenomenon. In all four examples mentioned above, democracy, popular sovereignty and direct plebiscitary appeal to the people is the rhetorical and justificatory framework for constitutional reform. This, I worry, gives democracy a bad name and reinforces the widespread suspicion that citizens should not be directly involved in constitutional reform as popular participation can lead to dangerous majoritarianism and is easily manipulated by elite actors seeking to weaken constitutional checks and balances. But the problem, I argue, is not inherent in citizen's participation in constitutional reform. In contrast to populist constitutionalism, I develop an idea of deliberative constitutionalism in which citizens can participate in constitution-making and reform without hijacking constitutionalism for majoritarian, nationalist or anti-pluralist ends. Deliberative constitutionalism as I understand it has four features: a Habermasian co-originality thesis that articulates the interdependence of democracy and liberalism mediated by a conception of discourse; a proceduralized idea of popular sovereignty that reduces the tension between appeal to the people and respect for pluralism; the centrality of the public sphere over the voting booth as the cradle of democracy; institutional innovations intended to include citizens in constitutional reform (including through referendums) but avoid majoritarian and populist pathologies.